Tingkat Kesejahteraan Rumah Tangga Nelayan Tangkap Pukat Tarik di Desa Sungai Nyirih Kecamatan Selakau - Andri, Revi; Saifullah, Saifullah; Yunita, Nurul Fatimah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Sungai Nyirih Village is one of the villages located in the Selakau District. The lack of income obtained by fishermen is a problem that is often experienced by fishermen when going to sea. The quality of life of the fishing community can be known by measuring the level of welfare. This study aims to determine how the level of welfare of fishermen households and how much the average net income of households of Trawl Catch Fishermen in Sungai Nyirih Village, Selakau District. In the research, the method used is using quantitative descriptive method. The research was conducted in Sungai Nyirih Village, Selakau District. Data collection techniques in this study used survey techniques. The data analysis technique used is using the Validity and Reability test analysis technique and Descriptive Statistical data analysis of the Welfare Level. The indicator of the welfare of households of trawl fishermen in Sungai Nyirih Village has a total score of 22 and has a high level of welfare and the net income of households of trawl fishermen is low because the income is only Rp.629,000. based on the results of measuring the level of welfare of 56 households of trawl fishermen in Sungai Nyirih Village using 8 (eight) indicators. The measurement results obtained that the level of welfare is classified in the high category with an average score of 21. Based on the review of the results and discussion of the research, it can be concluded that the average net income of households of trawl fishermen in Sungai Nyirih Village is Rp.629,250.